Continuous flow based catch and release protocol for the synthesis of α-ketoesters - Palmieri, Alessandro (Beilstein-Institut, 2009)
Using a combination of commercially available mesofluidic flow equipment and tubes packed with immobilised reagents and scavengers, a new synthesis of α-ketoesters is reported.